Image-Guided High-Dose Rate Brachytherapy in Cervix Carcinoma Using Balloon Catheter and Belt Immobilization System. (June 2017) - Fan, Qiyong; Yeung, Anamaria R.; Amdur, Robert; Helmig, Richard; Park, Justin; Li, Jonathan; Kahler, Darren; Liu, Chihray; Lu, Bo
Purpose: The efficacy of image-guided high-dose rate brachytherapy for cervical cancer is limited by the ineffective rectal sparing devices available commercially and the potential applicator movement. We developed a novel device using a balloon catheter and a belt immobilization system, serving for rectal dose reduction and applicator immobilization purposes, respectively. Methods: The balloon catheter is constructed by gluing a short inflatable tube to a long regular open-end catheter. Contrast agent (10) cm 3 is injected into the inflatable end, which is affixed to the tandem and ring applicator, to displace the posterior vaginal wall. The belt immobilization system consists of a specially designed bracket that can hold and fix itself to the applicator, a diaper-like Velcro fastener package used for connecting the patient's pelvis to the bracket, and a buckle that holds the fasteners to stabilize the whole system. The treatment data for 21 patients with cervical cancer using both balloon catheter and belt immobilization system were retrospectively analyzed. Computed tomography and magnetic resonance images, acquired about 30 minutes apart, were registered to evaluate the effectiveness of the immobilization system. Results: In comparison with a virtual rectal blade, the balloon decreased the rectal point dose by 34% ± 4.2% (from 276 ± 57 to 182 ± 38 cGy), corresponding to an extra sparing distance of 7.9 ± 1.1 mm. The maximum sparing distance variation per patient is 1.4 ± 0.6 mm, indicating the high interfractional reproducibility for rectum sparing. With the immobilization system, the mean translational and rotational displacements of the applicator set are <3 mm and <1.5°, respectively, in all directions. Conclusions: The rectal balloon provides significant dose reduction to the rectum and it may potentially minimize patient discomfort. The immobilization system permits almost no movement of the applicator during treatment. This work has the potential to be promoted as a standardized solution for high-dose rate treatment of cervical cancer.